Law Learning, Teacher-Student Relations, and the Legal Profession - Robert S. Redmount (Washington University Law Quarterly, 1981)
Innovation and change in legal education, extending the scope of the enterprise as it is now conducted, appear essential to strong moral, intellectual, and social purpose.
Keywords: Lawyers; Legal education; Teacher-student relations; United States